2014
DOI: 10.1002/alr.21467
|View full text |Cite
|
Sign up to set email alerts
|

Impact of saline irrigation and topical corticosteroids on the postsurgical sinonasal microbiota

Abstract: Introduction Topical treatments with nasal saline irrigation, topical steroid sprays, or corticosteroid rinses can improve sinonasal symptoms in chronic rhinosinusitis (CRS). However, the impact of these therapies on commensals (Corynebacterium) and on biofilm pathogens associated with CRS (Staphylococcus aureus and Pseudomonas) is not well characterized. Methods Paired nasal and sinus swabs were collected endoscopically from 28 controls and 14 CRS patients with nasal polyposis (CRSwNP) who had not received … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 22 publications
1
27
0
Order By: Relevance
“…Interestingly, in the first study, a number of patient-specific factors were examined, and the use of topical saline or topical intranasal steroids, or the presence of nasal polyps was not a predictor of altered microbiome composition. Similar findings were noted in a cross-sectional cohort of postoperative CRS with polyp patients, where the use of saline irrigations with or without budesonide was not found to influence the sinus microbiome [35]. To date, properly designed studies to evaluate for the effect of topical therapies on the microbiome have not been performed, so no real conclusions can be made.…”
Section: Current Sinus Microbiome Literature Reviewsupporting
confidence: 59%
“…Interestingly, in the first study, a number of patient-specific factors were examined, and the use of topical saline or topical intranasal steroids, or the presence of nasal polyps was not a predictor of altered microbiome composition. Similar findings were noted in a cross-sectional cohort of postoperative CRS with polyp patients, where the use of saline irrigations with or without budesonide was not found to influence the sinus microbiome [35]. To date, properly designed studies to evaluate for the effect of topical therapies on the microbiome have not been performed, so no real conclusions can be made.…”
Section: Current Sinus Microbiome Literature Reviewsupporting
confidence: 59%
“…Clinical trials and meta‐analyses have shown that saline alone irrigation is effective for reducing CRS symptoms and improving QOL in both pre‐operative and post‐operative periods . We compared the effects of saline irrigation with steroid treatment with saline irrigation alone.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials and meta-analyses have shown that saline alone irrigation is effective for reducing CRS symptoms and improving QOL in both pre-operative and post-operative periods. 23 We compared the effects of saline irrigation with steroid treatment with saline irrigation alone. Steroid irrigation was not associated with significant improvements in the measurements, compared to saline irrigation, which could be explained by several reasons.…”
Section: Improvement Of Outcomesmentioning
confidence: 99%
“…449,450 Observed alterations in local microbiota in CRS may result from repeated and prolonged medical therapies. 439,451 In the Feazel et al 439 study, prior sinus surgery and the presence of S. aureus were also associated with less diversity, but this observation requires further exploration to determine if this is a disease-association or a result of the extensive medical and surgical therapies used in recalcitrant CRS.…”
Section: S63mentioning
confidence: 99%